Jealous Murderers as Reflected in Shakespeareâs Othello: A Psychoanalytic Study - Fainuddin, Nuri (Universitas Ahmad Dahlan, 2015)
AbstractThis analysis describes the main charactersâ jealous murder and their id, ego and super ego. It tries to describe the moral teachings of the drama. Desdemona was killed by her own husband, Othello, because of jealousy. He received Iagoâs report that Desdemona had an affair with Cassio.Â Iago made issues that Desdemona had an affair with Cassio because he felt jealous that Cassio was promoted to be a lieutenant. Iago asked Roderigo to kill Cassio but failed. Roderigo was killed by Iago, to omit the traces.Sigmund Freudâs theory of id, ego, and super ego will be used in analyzing the problems. The subject of this analysis is drama Othello, and the object of this analysis is a psychoanalyticÂ study with its id, ego and super ego.The research findings are : jealous murders that had been done by Othello and Iago. Othelloâs isÂ murderingÂ his own beautiful wife, Desdemona, without further checking. To omit the trace, Iago killed Roderigo, the person that he asked to kill Casio; It is Iago âs id. Othelloâs ego is when he received news from Iagoâs wife, Emilia. She told the truth to Othello that Iago was the person who asked her to steal Desdemonaâs handkerchief. Othello felt that he had made mistakes and the he punished Iago by stabbing him.Â Othelloâs super ego is his feeling regret after receiving news fromÂ Iagoâs wife, Emilia. The moral teachings of the drama are (1) people should screen news they received, and (2) people should avoid of being jealous.